IN VITRO DIAGNOSIS METHOD FOR PERIODONTAL DISEASES, AND PG BACTERIUM DETECTION METHOD - NARADASU Divya; OKAMOTO Akihiro (2024)
The in vitro diagnostic method for periodontal disease of the present invention includes bringing a sample derived from an oral cavity of a subject into contact with an electrode to perform electrochemical measurement in the presence of a glucogenic amino acid and an electron mediator under an anaerobic environment and providing information for judging that periodontal disease is progressing in the oral cavity of the subject when current generation is detected as a result of the electrochemical measurement. According to the in vitro diagnostic method for periodontal disease of the present invention, it is possible to provide information for judging the progress of periodontal disease by simple operation.